Power, institutions, and state-building after war: A controlled comparison of Rwanda and Burundi - Omar McDoom (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
I examine whether and how the means through which a civil war ends affects the success of a country's state-building strategy after conflict. I show that two distinct modes of conflict termination-military victories and negotiated settlements-lead to differential long-run statebuilding outcomes and offer an explanation of the mechanism behind the divergence. In a military victory, the coercive balance-of-power at the end of war favourable to the victor enables it to dictate the post-conflict institutional design and skew power formally in its favour. In a negotiated settlement, formal power is distributed by design among multiple parties to avoid the dominance of any single actor. These differences in turn have implications for the distribution of informal power in the post-war context whose influence is exercised through private networks of party members and loyalists. Informal power becomes concentrated in the victorious party because its opponent is typically excluded from the post-conflict political process and expelled from the territory. In contrast, in negotiated settlements informal power is commonly diffuse because the inclusion of erstwhile military rivals in the political process enables the operation of multiple informal networks that then compete for influence. I suggest that when both formal and informal power become concentrated in a single actor-a militarily victorious party-power may even become hegemonic. The dominance of the victorious party is assured because the basis of its rule becomes both coercion and consent. This mutes resistance to its post-conflict agenda and, consequently, strengthens its capacity to implement its state-building strategy. I trace this causal process over a period of two decades through a controlled comparison of Rwanda and Burundi whose civil wars terminated through military victory and negotiated settlement, respectively. The findings have implications for theories of liberal peacebuilding, institutional independence, and the distribution of power in post-conflict contexts.
Keywords: D74; F51; F53; 330; civil wars; negotiated settlements; state-building